2002
DOI: 10.1007/s00412-002-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a novel satellite DNA family highly conserved in several Cervidae species

Abstract: In an attempt to amplify cervid satellite II DNA from the genomes of Indian muntjac and Chinese muntjac, a pair of primers derived from the white tailed deer satellite II DNA clone (OvDII) yielded a prominent 1 kb polymerase chain reaction (PCR) product (in addition to the expected 0.7 kb satellite II DNA fragments) in both species. The ~1 kb products were cloned, sequenced, and analyzed by Southern blotting and fluorescence in situ hybridization (FISH). This revealed that thẽ 1 kb cloned sequences indeed repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 24 publications
6
27
1
Order By: Relevance
“…BM1.1k had a length of 1.1-kbp with 44.27% GC content. Multiple-alignment was performed among BM1.1k, MMV-1.0 (M. muntjak vaginalis satellite IV), MR-1.0 (M. reevesi satellite IV) (Li et al, 2002), and FM-sat IV (M. reevesi micrurus satellite IV) (Lin et al, 2004), 98.17% homology was found among these clones (Fig. 2e), suggesting that BM1.1k belongs to the satellite IV DNA family.…”
Section: Molecular Cloning and Characterization Of Satellite I Ii Imentioning
confidence: 99%
See 2 more Smart Citations
“…BM1.1k had a length of 1.1-kbp with 44.27% GC content. Multiple-alignment was performed among BM1.1k, MMV-1.0 (M. muntjak vaginalis satellite IV), MR-1.0 (M. reevesi satellite IV) (Li et al, 2002), and FM-sat IV (M. reevesi micrurus satellite IV) (Lin et al, 2004), 98.17% homology was found among these clones (Fig. 2e), suggesting that BM1.1k belongs to the satellite IV DNA family.…”
Section: Molecular Cloning and Characterization Of Satellite I Ii Imentioning
confidence: 99%
“…The products were fractionated on a 1.5% agarose gel. Three bands of 0.7, 1.1 and 1.4 kb are detected in these species; b: Schematic illustration of sequence comparison between M. crinifrons satellite II DNA clone (BM700) and Formosan muntjac satellite II clone (FM-satII); c: Schematic diagram DNA sequences comparison between M. feae satellite DNA II clone (FM700) and Formosan muntjac satellite II clone (FM-satII); d: Multiple-alignment of M. crinifrons satellite II clone (BM700), M. feae satellite II clone (FM700) and M. muntjak vaginalis satellite II clone (MMV-0.7) shows 85.69% homology (identical nucleotide sequences from these clones are shown in black boxes); e: Multiple-alignment of M. crinifrons satellite IV clone (BM1.1k), MMV-1.0 (M. muntjak vaginalis satellite IV) (Li et al, 2002), MR-1.0 (M. reevesi satellite IV) (Li et al, 2002), and FM-sat IV (M. reevesi micrurus satellite IV) (Lin et al, 2004) shows 98.17% similarity.…”
Section: Chromosome Distribution Of Satellite I (Bmc5) Satellite Ii mentioning
confidence: 99%
See 1 more Smart Citation
“…All duplicated microclones were lifted onto nylon membranes and denatured in an alkali solution. A probe mixture containing 32 P-labeled satellite I (C5; (Lin et al 1991)), satellite II (Mmv-0.7; (Li et al 2000b)) , satellite IV (Mmv-1.0; (Li et al 2002)), and satellite V (Mmv-0.32#1; (Li et al 2005)) was used to hybridize the membranes for the first screening. A 32 P-labeled DOP-PCR amplified X + 3-microdissected DNA probe was used to hybridize the membranes for the second screening.…”
Section: Isolation Of a Novel Cervid Centromeric Dna Clonementioning
confidence: 99%
“…The centromeric/pericentromeric region of the Indian muntjac (Muntiacus muntjak vaginalis; barking deer) chromosome X + 3 is known to be exceptionally huge and compound in nature (Brinkley et al 1984) and may be composed of many different satellite DNA families (including functional centromeric and nonfunctional centromeric satellite DNAs as well as new and old satellite DNAs). Indeed, cervid satellite I (an old cervid satellite DNA) (Lee et al 1994;Lin et al 1991), cervid satellite II (a functional centromeric satellite DNA) (Vafa et al 1999;Li et al 2000b), and cervid satellite IV (Li et al 2002) had been found in the X + 3 centromere region of Indian muntjac.…”
mentioning
confidence: 99%